(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
It is clear to all of us that in the period of independence, the art of musical performance, culture and its promotion, like all other fields, is growing according to the demands of the times, is on the path of development, and is getting polished. The performance art of national musical instruments of a new direction corresponding to world standards has significantly formed, improved and grown. At the same time, if we take into account that the new generation of teachers is increasing, we can emphasize that in Uzbekistan the music performance art is rising to a new level of quality.